Analysis on the relationship between sectoral electricity consumption, economics performance and electricity price in Malaysia - Mohd Hafiz Aswad, Nadzri (2015)
Electricity is one of the important sources of energy and is vital for the process of the country’s economic growth. The issues of growing electricity consumption and heavy electricity subsidies have raised the attention of the government. However, the majority of the previous studies that specialize on the demand side of electricity were focused on total electricity consumption. Thus, this paper aims to provide the background analysis of electricity consumption trends with the focus on the four main economic sectors in Malaysia such as the industrial, commercial, mining and agricultural. The purposes were to examine the relationship between electricity consumption, Gross Domestic Product (GDP) and price of electricity based on panel data for the period 2002 to 2012. The sectoral electricity consumption model was tested using econometric techniques such as Panel Cointegration, Panel Fully Modified Ordinary Least Square (FMOLS) and Panel Granger Causality tests. The Panel Cointegration Test confirmed an existence of a stable long run relationship among the variables. The results from the panel FMOLS estimation revealed that the electricity consumption in industrial, commercial and mining sectors was positively responsive to GDP changes. In the agricultural sector, GDP had a negative effect on electricity consumption. Moreover, the higher electricity price tended to increase and decrease electricity consumption in the industrial sector and commercial sector respectively. Nonetheless, the results of the electricity price were not significant in the mining and agricultural sectors. For all the sectors, an increase in GDP had a positive effect on electricity consumption. Finally, the Panel Granger Causality Test detected a relationship running from economic growth to electricity consumption. The results obtained indicated that policy maker must be careful in the formulation of energy policy, thus suggesting that the policy should be focused on the electricity consumption in each sector